Kebijakan Hukum Vrijwillige Orderwepping Dan Toepasselijk Verklaring Sebagai Unifikasi Pemerintah Hindia Belanda - Entol Zaenal Muttaqin; Ahmad Zaini (Fakultas Hukum Universitas Islam Indonesia, 2021)
This paper aims firstly, to identify the background of how the Vrijwillige Onderwepping and Toepasselijk Verklaring policies are made. Second, to explore the influence of the policies of Vrijwillige Onderwepping and Toepasselijk Verklaring in realizing legal unification in the Dutch East Indies. The method used is normative juridical with statutory and historical approaches. At the end this paper concludes that, First, the vrijwillige onderwepping and toepasselijk verklaring policies were made to bridge two different perspectives even though the ultimate goal is unification. Second, this policy greatly influenced the submission of the natives to European law although complete unification was never achieved due to the arrival of the Japan in 1942.